Environmental education in higher education institutes in Asia: overview of experiences in South Korea, Malaysia, and Japan - Sachi, Ninomiya-Lim; Kang, Jinyoung; Kim, Changhwan; Abdullah, Sabrina J. Ho (Routledge, 2019)
This paper provides an overview of the development and status of environmental education (EE) at higher education institutes (HEIs) in three Asian countries: South Korea, Malaysia, and Japan. EE is one of the major educational fields oriented toward sustainability, and a mutual understanding of EE in HEIs among different Asian countries is considered to be crucial for successful international collaboration toward sustainability. The paper, based on a review of existing documents and data, presents an overview of EE at HEIs in these countries, particularly at universities and teacher-training institutes, according to a four-category framework, and recommends topics that should be further explored in the interest of successful international collaboration toward a sustainable future.